Energy Dependence of Underdeveloped Countries - Morett Sánchez, Jesús Carlos (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2021)
In the present stage of globalization of the economy, underdeveloped countries are still further away from achieving solid, sustainable and balanced economic growth, which will enable them to escape from poverty and reduce social inequalities. They are nations where backwardness has increased and tends to be perpetuated for various reasons, one of them being the inability to generate most of the fuels and energy required in economic activities, transportation, public services and homes with its own resources. So that, the objective of the article is to determine the energy dependence of underdeveloped countries, based on the magnitude of their deficit in the energy balance, to show that this situation constitutes an obstacle to their progress.